Evaluation of Yield and Yield Contributing Characters of Heat Tolerant Potato (Solanum tuberosum L.) Genotypes in Bangladesh - Rahman, MH; Alam Patwary, MM; Barua, H; Hossain, M; Nahar, S (The Agriculturists, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Eight heat tolerant CIP (International Potato Centre) potato genotypes along with BARI (Bangladesh Agricultural Research Institute) Alu-7 (Diamant) and one local variety (Dohazari Sada) were evaluated at Agricultural Research Station, Pahartali, Chittagong during 2011-12 to identify heat tolerant genotypes from varieties and CIP clones of potato. Diamant and Dohazari Sada and all the heat tolerant CIP genotypes were found to grow well up to 60 DAP (days after planting) against heat having healthy plants and no senescence was noticed. After that 61-100% plants died due to high temperature (29.8oC) depending on the genotypes. Genotype CIP 139 gave the highest yield (14.18 t/ha) and was comparatively less affected by heat than the other genotypes. The high dry matter (22.43 %) accumulated in the local variety Dohazari Sada. DOI: http://dx.doi.org/10.3329/agric.v12i1.19580 <span style="font-size: 12.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Agriculturists <span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2014<span style="font-size: 12.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">; 1<span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2(1) 50-55<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->